PERAN KELUARGA DALAM PERILAKU PEMBELIAN HEDONIS - Sigit Wibawanto (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2018)
This study aims to examine the structure of the family's role in the lifestyle of hedonism and its influence on the consumer purchasing process. Observation activities are carried out at modern markets and cafes/ restaurants in Kebumen district. This research paradigm discusses aspects of consumer behavior and marketing research regarding consumer behavior and purchasing decisions that vary and reflect the hedonic dimension. This descriptive qualitative research conducted with the purpose to understand the meaning symbolized by each family's behavior according to the family's own perspective. The results of the study show that shopping locations can cause a shift in purchasing activities in modern markets lead to hedonic behavior, but are still relatively normal. In the visit activities at cafe/ restaurant show hedonic behavior because it provides an illustration that eating outside the home as a place of discussion is considered interesting, not up to date, luxurious and worth displaying on its social media accounts. This research shows a number of the propositions that apply in the field. This research still needs to be improved, especially in the discussion of objects and research locations, including the selection of entertainment/ tourism places, as well as family strata in influencing hedonic buying behavior. Keywords: buying behavior, hedonic lifestyle, family role, modern market, cafe/ restaurant